INVESTIGATION OF HOT MIX ASPHALT PROPERTIES WITH INCORPORATION OF CRUMB TYRE AND POLYCARBONATE - Joseph, Oyedepo Olugbenga; Adekunle, Adewuyi Abiodun; Jayejeje, Omomomi Oladapo (Journal of Civil Engineering, Science and Technology, 2024)
Asphalt, a crucial material in construction, demands constant improvement to meet evolving infrastructure requirements. This research addressed the need for enhancing asphalt properties by incorporating crumb tyre, crumb polycarbonate, and their combined formulation as additives. The objective was to modify bitumen properties for optimized asphalt production, specifically focusing on strength characteristics. The study employed a comprehensive methodology to assess the impact of these additives on bitumen. It examined their influence on penetration, ductility, softening point, viscosity, and thermal stability, particularly the flash and fire points. Various proportions of additives were investigated, seeking the most effective composition. The results of this research unveil promising outcomes. The additives exerted a stiffening effect on bitumen, altering its molecular structure and intermolecular interactions. Consequently, penetration values decreased, indicating enhanced stiffness. Moreover, ductility significantly increased, suggesting improved resistance to deformation. Furthermore, the softening point of bitumen rose, indicating heightened resistance to softening at elevated temperatures. The viscosity of bitumen decreased upon additive introduction, simplifying mixing with aggregates during asphalt production. The additives also elevated the flash and fire points, signifying enhanced thermal stability. Based on these findings, the recommended mix consists of 10% crumb tyre, 10% crumb polycarbonate, and 10% of both additives combined. This composition outperforms other proportions, presenting a viable solution to enhance asphalt properties for a wide range of road applications.